Methanolysis of ammonia borane using binder‐free hierarchical Co@Ni metal‐organic framework nanocolumn arrays catalyst for hydrogen generation. (1st August 2022) - Kumar, Dharman Ranjith; Prabu, Samikannu; Chiang, Kung‐Yuh; Oh, Tae Hwan
Summary: Ammonia borane (AB) is a potential material for chemical hydrogen storage because of its outstanding stability, high hydrogen density, and the development of highly effective hierarchical catalysts for AB hydrolysis. Herein, the hierarchical Co@Ni metal‐organic framework (MOF) nanocolumn arrays (NCAs) on nickel foam (NF) were fabricated through a simple hydrothermal reaction, and the prepared catalysts were characterized using different techniques. The hierarchical Co@Ni‐MOFNCA/NF acts as a catalyst for AB methanolysis for hydrogen production. The catalysts exhibited outstanding performance towards AB methanolysis with the TOF of TOF of 20.54 mol H2 mol catalyst −1  min −1 . As a result, the activation energy of the Co@Ni‐MOF NCA catalyst is 39.72 kJ mol −1 which is compared with some commercial solid support materials such as Al2 O3 and AC. Additionally, the effects of nanocatalyst loading and temperatures were studied for the Co@Ni‐MOF NCA catalyst. Further, a complete investigation proposes that the outstanding catalytic performance of the Co@Ni‐MOF NCA catalyst could be attributed to the synergy between Co and Ni‐MOF NCA. Abstract : Ammonia borane (AB) is a potential material for chemicalhydrogen storage because of its outstanding stability, high hydrogen density, and the development of highly effective hierarchical catalysts for ABhydrolysis. Herein, the hierarchical Co@Ni metal‐organic framework (MOF)nanocolumn arrays (NCAs) on Ni foam (NF) were fabricated through a simplehydrothermal reaction, and the prepared catalysts were characterized usingdifferent techniques.